PEMBERDAYAAN JAMAAH MASJID DAN PENANGGULANGAN DAMPAK PANDEMI COVID-19 - Hidayat Muttaqin; Khaerul Wahidin; Muhammad Azka Maulana; Juju Juarsih (An-Nufus, 2020)
This article discusses the impact of the Covid-19 pandemic on the spiritual life of Muslims in the mosque environment. It cannot be avoided if the Corona outbreak also has a major impact on the religious sector, especially in mosques, so it needs a separate formula for dealing with it. Moreover, people in Indonesia are known to be religious and used to busy themselves massively in places of worship such as prayer rooms and mosques. While on the other hand, the crowd aspect is something that must be avoided to avoid contracting the Corona virus lately. For this reason, this study aims to determine how to empower mosque congregations in overcoming the impact of Covid 19; in this case the empowerment of congregation at the Baitul Mukhlisin Mosque in Pangkalan Village, Ciawigebang District, Kuningan, West Java. The method used in this research is an action research method, a combination of data collection and processing in an integrated manner. From the results of this study found a solution to the controversy that occurred among the congregation by building a synergy between DKM of the Baitul Mukhlisin Mosque and IREMA BM as well as religious leaders using a persuasive approach to foster a spirit of cooperation and produce mutual agreement.